[PP.02.10] EFFECT OF DIFFERENT TYPES OF COMBINED THERAPY ON CENTRAL BP AND ARTERIAL STIFFNESS IN PATIENTS WITH MODERATE TO SEVERE AH: RESULTS OF A PROSPECTIVE RANDOMIZED OPEN LABEL TRIAL. (September 2017) - Torbas, O.; Sirenko, Y.; Radchenko, G.
Abstract : Objective: It is well known that the effectiveness of medications prescribed alone or as a combination may be different. The purpose of this study was to compare the effectiveness of therapy based on a combination of highly selective beta-blocker bisoprolol and hydrochlorothiazide (B+HCTZ) with a combination of well-known with sufficient evidence base ACEI lisinopril and hydrochlorothiazide (Liz+HCTZ) or ARB losartan and hydrochlorthiazide (Los+HCTZ). Figure. No caption available. Design and method: In this 6-month trial we included 91 patients with AH (mean systolic (oSBP)/diastolic (oDBP) BP 168, 4 ± 1, 5/99, 6 ± 1, 0 mmHg): 32 in losartan 100 mg + hydrochlorothiazide 25 mg (Los + HCTZ), 32 in lisinopril 40 mg + hydrochlorothiazide 25 mg (Liz + HCTZ) and 27 in bisoprolol 10mg + hydrochlorothiazide 25 mg (B + HCTZ). All patients at baseline and during follow-up underwent: (office) oSBP, oDBP and HR mesasurement, ABPM, noninvasive central SBP (cSBP) measurement and evaluation of carotid-femoral (cfPWV) and carotid-radial (crPWV) pulse wave velocity, biochemical blood tests. If blood pressure after 1 month of treatment was higher than 140/90 mmHg amlodipine 5 mg was added, if it was insufficient the dose of amlodipine was increased to 10 mg after 2 months. After 3 months, if necessary, doxazosin 2–4 mg was added. Results: Decrease of oSBP/DBP was similar in Los + HCTZ, Liz + HCTZ and B + HCTZ groups (44, 7 ± 0, 9/18, 4 ± 1, 1 mmHg, 44, 5 ± 1, 9/19, 0 ± 2, 1 and 42, 4 ± 2, 1/18, 8 ± 2, 5 mmHg in each group respectively, P = NS for difference between groups). The percentage of patients achieved target BP were 96, 9% in Los + HCTZ, 93, 8% in Liz + HCTZ and 92, 6% in B + HCTZ groups. 24SBP/24DBP decreased by 24, 6 ± 1, 3/17, 6 ± 1, 1 mmHg in Los + HCTZ, 19, 0 ± 3, 3/19, 3 ± 2, 8 mmHg in Liz + HCTZ group and by 24, 1 ± 1, 8/16, 9 ± 1, 2 mmHg in B + HCTZ group, in addition, we observed a significant reduction in average HR in this group. Dynamics of cSBP, Aix and PWV are illustrated on the picture. Reduction of cSBP in Los + HCTZ and in Liz + HCTZ groups was significantly higher than in group of bisoprolol-based combination. Conclusions: Despite of the almost equivalent brachial BP decrease according to office measurement and according to ABPM data, therapy based on combinations of Los + HCTZ Liz + HCTZ significantly better decreased cSBP.